PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IVA SDN 015 BANJAR XII KECAMATAN TANAH PUTIH - ', Herniati; Alpusari, Mahmud; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem this research is the students achievment of science studies SD Negeri 015 Banjar XII fourth A graderes still low with an average value of 62,70 and minimum completenness criteria (KKM) social studies is 70. Between students, amounting to 24 people only 10 students who achieve classical KKM with 41,67%. This research is Classroom Action Research (CAR), wich aims to improve the student achievement of science studies class fourth A at SD Negeri 015Banjar XII with implementation model cooperative learning type Think Pair Share. Formulation of the problem: is the implementation of model cooperative learning type Think Pair Share can improve students achievment of science studies at SD Negeri 015 Banjar XIIfourth A graderes?. The research was conducted on April to May 2016 by 2 cycles. Subjects were students of SD Negeri 015 Banjar XIIfourth A graderes, totalling 24 people who use the data source. The data collection instruments in this thesis is a teacher and students activities sheets and students achievement. Activities of the teacher in the learning process in cycle I the first meeting to 66,6% and the second meeting improve to 75%. Cycle II first meeting and the second meeting improve 87,5% and the second meeting improve to 95,8%. Result of data analysis of students activities in the first meeting cycle with the first meeting of an avarage of 58,3% and a second meeting improve to 66,6%. Cycle II first meeting improve 83,3% and the second meeting improve to 95,8%. This thesis presents the results obtained each day before the action an improve in base score sycle with the average being 62,70. In the first cycle improve an average of 72,92 with increase big as 16,30% and an impove in the second with an average of 83,54 with increase big as 33,24%. Result in the class fourth A at SD Negeri 015 Banjar XII that the implementation of model cooperative learning type Think Pair Share can improve students achievement of science Studies at fourth A graderes SD Negeri 015 Banjar XII. Key Word : Cooperative Learning, Think Pair Share, Result Of Science Studies